The Word in the Desert : Scripture and the Quest for Holiness in Early Christian Monasticism - Burton-Christie, Douglas (New York : Oxford University Press, 1993)
The growing scholarly attention in recent years to the religious world of late antiquity has focused new attention on the quest for holiness by the strange, compelling, often obscure early Christian monks known as the desert fathers. Yet until now, little attention has been given to one of the most vital dimensions of their spirituality: their astute, penetrating interpretation of Scripture. Rooted in solitude, cultivated in an atmosphere of silence, oriented toward the practical appropriation of the sacred texts, the desert fathers' hermeneutic profoundly shaped every aspect of their lives and became a significant part of their legacy. This book explores the setting within which the early monastic movement emerged, the interpretive process at the center of the desert fathers' quest for holiness, and the intricate patterns of meaning woven into their words and their lives. - Publisher.
Keywords: Patristics (3Yde GdBHGFjGJs; Patrology -- Monasticism and religious orders -- Egypt -- History; Monasticism and religious orders -- History -- Early church, ca. 30-600.